2019
DOI: 10.3389/fnins.2019.00645
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SNHG12 Enhanced the Effectiveness of MSCs in Alleviating Ischemia/Reperfusion Injuries via the PI3K/AKT/mTOR Signaling Pathway

Abstract: Previous studies have reported that the long non-coding RNA SNHG12 (lncRNA SNHG12) plays a critical role in regulating the function of mesenchymal stem cells (MSCs); however, the effect of lncRNA SNHG12 on MSCs in injured brain tissue has rarely been reported. We studied the effect and mechanism of lncRNA SNHG12-modified mesenchymal stem cells (MSCs) in treating brain injuries caused by ischemia/reperfusion (I/R). I/R treated rat brain microvascular endothelial cells (BMECs) were co-cultured with MSCs or I/R p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
(42 reference statements)
1
31
0
Order By: Relevance
“…Transwell co-culture system plates (Corning, USA) were used to co-culture BV2 microglial cells with OM-MSCs for 24 hours. The co-cultured cells were used for subsequent experiments according to previously described protocols [42].…”
Section: Co-culture Of Om-mscs With Bv2 Microglial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transwell co-culture system plates (Corning, USA) were used to co-culture BV2 microglial cells with OM-MSCs for 24 hours. The co-cultured cells were used for subsequent experiments according to previously described protocols [42].…”
Section: Co-culture Of Om-mscs With Bv2 Microglial Cellsmentioning
confidence: 99%
“…Western blotting was performed as previously described [42]. Briefly, the cell samples were lysed using RIPA Lysis Buffer (Beyotime, China) according to the manufacturer's instruction.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The pathogenesis of ischemic stroke is brain tissue ischemia, hypoxia, and lack of energy in secondary brain tissue, causing a pathological state of energy metabolism disorder, oxidative stress damage, apoptosis, and other effects 22 . In the present study, we used an MCAO rat model and OGD/R cell model to determine the effects of PF + CG following acute ischemic stroke through the activation of the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SnHG12, small nucleolar rna host gene 12; oGd, oxygen-glucose deprivation; mir or mirna, microrna; neGr1, neuronal growth regulator 1; si, small interfering; Bcl-2, B-cell lymphoma 2; Bax, Bcl-2 associated X protein; MT, mutant; WT, wild-type; nc, negative control aMP-activated protein kinase (aMPK) signaling pathway under oxygen-glucose deprivation/reoxygenation conditions. Furthermore, silencing SnHG12 enhanced the effects of mesenchymal stem cells by reducing apoptosis and autophagy of brain microvascular endothelial cells by activating the phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin signaling pathway (34). SnHG12 functions as a cerna for mir-150 to mediate VeGF expression and promote angiogenesis and alleviate ischemic stroke (23).…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al ( 21 ) reported that SNHG12 interacted with miR-199a to attenuate apoptosis and cerebral ischemia/reperfusion injury via the AMP-activated protein kinase (AMPK) signaling pathway under oxygen-glucose deprivation/reoxygenation conditions. Furthermore, silencing SNHG12 enhanced the effects of mesenchymal stem cells by reducing apoptosis and autophagy of brain microvascular endothelial cells by activating the phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin signaling pathway ( 34 ). SNHG12 functions as a ceRNA for miR-150 to mediate VEGF expression and promote angiogenesis and alleviate ischemic stroke ( 23 ).…”
Section: Discussionmentioning
confidence: 99%